Decentralization and Service Delivery in Albania : Governance in the Water Sector - World Bank (Washington, DC, 2013)
This review of the water sector in Albania was prepared as a background paper to the World Bank s Country Partnership Strategy for Albania for 2011-2014. It draws on past analytical work on decentralization in Albania as well as relevant World Bank-financed operations such as the Water Sector Investment Project. Over the past decade, the World Bank has intensified its focus on governance as a key factor accounting for variations in development effectiveness. Through its long-standing engagement in Albania, the World Bank has supported institutional development and governance reforms to help strengthen the capacity of state institutions to deliver public goods and achieve development outcomes more effectively and efficiently. Governance is a key pillar of the Government s National Strategy for Development and Integration for 2007-2013. In an effort to improve the performance of water supply and wastewater services, the Government has designed reforms on the basis of international best practice. In spite of these well-intentioned policy decisions, utility performance has been disappointing, in part because of excessively complex design and implementation of sector governance arrangements. There is a need to address water sector governance on several fronts - legal, institutional, economic, administrative, and social - all of which have implications for service performance.